Crowdfunding: Determinants of success and funding dynamics - Paolo Crosetto; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
Over the past years crowdfunding emerged as an alternative funding channel for entrepreneurs. In contrast to traditional financiers (banks, venture capital firms or angel investors), crowdfunding allows individuals to fund entrepreneurs directly even with small amounts. We received individual-level data from Startnext, the biggest crowdfunding platform in Germany, enabling us to investigate funding dynamics, explore pledgers' motivations and analyze projects' success determinants. We find substantial heterogeneity of how success (about half of the 2,252 projects in our dataset get funded) is reached. When two thirds of the funding duration has passed, the majority of projects (59%) that eventually get funded are not on a successful track. However, pledges in the final phase can only partially be explained by a rush to get still unfunded projects succeed. Overall, 18.7% of pledges are made to projects that already reached their funding target and our analysis shows that the increased funding towards the deadline is due to pledges to projects that already made it, particularly pre-selling pledges.
Keywords: D0; G32; 330; crowdfunding; donations; entrepreneurial finance; pre-selling